Political Communication Capacity Building Young Cadres of DPD Golkar Party Bandung District - Kurniawati, Nia (Universitas Pancasakti Tegal, 2022)
This PKM activity aims to improve the political communication skills of the Young Cadres of DPD Golkar Party Bandung Regency through political education. Political education is carried out through technical guidance with material on